РАЗВИТИЕ ИНФОРМАЦИОННО-БИБЛИОТЕЧНОЙ СРЕДЫ СО РАН в 2007-2009 гг. ДЛЯ ОБЕСПЕЧЕНИЯ НАУЧНЫХ КОММУНИКАЦИЙ (Библиосфера)
The results of the research project «Development of Information and Library System in SB RAS for scientific communications» in 2007-2009 are presented.